The healthy behaviours and COVID-19 mortality among Iranian women: a case-control study - Farhad Pourfarzi; Shima Rahim Pouran; Abdollah Dargahi; Chiman Karami; Nasrin Fouladi; Hamed Zandian; Telma Zahirian Moghadam (BMC, 2021)
Abstract Background Women are among the susceptible groups to Coronavirus disease-19 (COVID-19) in Ardabil, north-west of Iran, despite the current global status. The underlying causes of high incidence and fatality rate of women in Ardabil are not fully understood. Hence, this study aimed to investigate the healthy behaviours in women of Ardabil and its relationship with COVID-19 mortality. Methods We conducted a case-control study to compare the adherence to health protocols and behaviours with respect to COVID-19 between the infected (261 patients) and healthy (515 persons) women. Health protocols and behaviours such as using mask, gloves, disinfectants, history of travelling and contacting, and attending various gatherings and places during the COVID-19 pandemic along with demographic variables were defined as independent variables, and COVID-19 death rate was defined as the dependent variable. Multivariable logistic regression methods were used to explore the risk factors associated with COVID-19 mortality. Results Chi-square and Fisher tests showed significant differences between infected and healthy women in terms of history of contact and traveling (p < 0.05), wearing mask (p < 0.001), going to work place (p < 0.001), and attend public gatherings (p = 0.038). Multivariable logistic regression disclosed that the age group over 80 years: 8.97 times (95% CI 2.27-29.85), women with underlying chronic diseases: 4.14 times (95% CI 1.61-10.64), and obese women: 3.01 times (95% CI 1.04-6.03) were more likely to die from COVID-19 than other women. Conclusion Considering the high incidence and mortality rate in Ardabil women due to COVID-19 and the corresponding health behavioural factors, special emphasis should be given to the increase of women awareness on the importance of healthy behaviours, diet, and life-style.